Description of non-communicable diseases and risk factors related to lifestyle among POSBINDU (Integrated Guidance Posts) participants in Yogyakarta in 2022 - Poniasih, Ami; Sunarti, Sunarti; Sulistyawati, Sulistyawati; Rokhmayanti, Rokhmayanti (Universitas Ahmad Dahlan, 2024)
Non-communicable diseases are a public health problem and are a significant cause of death both in Indonesia and worldwide. These diseases cause a complication if not appropriately managed. Indonesian basic health research (Riskesdas) 2018 found that there was an increase in cases of non-communicable diseases compared to the previous research. One of the strategies used to control non-communicable diseases is by early detection of risk factors for non-communicable diseases through Posbindu activities. This research aims to describe the health status of participants of one Posbindu in 2022. This descriptive research uses secondary data from the results of examinations in 2022. The number of participants was 1,090 people consisting of 42.11% men and 57.89% women. The age range of the participants was 26-35 years with as many as 33.67%. Participants' highest education was undergraduate with as many as 50.09% and those with married status were 73.58%. Based on the Posbindu examination results, 578 people (53.03%) had central obesity, with 332 cases among female participants (57.44%). Posbindu participants with hypertension were 182 people where 119 of them were male (65.38%). Posbindu participants with diabetes mellitus were 30 people (2.75%), with the most cases in men, 21 (70%). Non-communicable diseases can affect anyone; the older you are, the more at risk you will get. One way to prevent non-communicable diseases is to control the risk factors such as smoking, lack of physical activity, excessive consumption of sugar and salt, and less consumption of vegetables and fruit. In the coming years, it is anticipated that further exploration will be undertaken, utilizing firsthand data collection methods, presenting findings descriptively, and employing inferential analysis techniques to draw meaningful conclusions.